Iron therapy mitigates chronic kidney disease progression by regulating intracellular iron status of kidney macrophages - Edwin Patiño; Divya Bhatia; Steven Z. Vance; Ada Antypiuk; Rie Uni; Chantalle A. Campbell; Carlo G. Castillo; Shahd Jaouni; Francesca Vinchi; Mary E. Choi; Oleh M. Akchurin (2022)
Systemic iron metabolism is disrupted in chronic kidney disease (CKD). However, little is known about local kidney iron homeostasis and its role in kidney fibrosis. Kidney-specific effects of iron therapy in CKD also remain elusive. Here, we elucidate the role of macrophage iron status in kidney fibrosis and demonstrate that it is a potential therapeutic target. In CKD, kidney macrophages exhibited depletion of labile iron pool (LIP) and induction of transferrin receptor 1, indicating intracellular iron deficiency. Low LIP in kidney macrophages was associated with their defective antioxidant response and proinflammatory polarization. Repletion of LIP in kidney macrophages through knockout of ferritin heavy chain (Fth1) reduced oxidative stress and mitigated fibrosis. Similar to Fth1 knockout, iron dextran therapy, through replenishing macrophage LIP, reduced oxidative stress, decreased the production of proinflammatory cytokines, and alleviated kidney fibrosis. Interestingly, iron markedly decreased TGF-β expression and suppressed TGF-β–driven fibrotic response of macrophages. Iron dextran therapy and FtH suppression had an additive protective effect against fibrosis. Adoptive transfer of iron-loaded macrophages alleviated kidney fibrosis, validating the protective effect of iron-replete macrophages in CKD. Thus, targeting intracellular iron deficiency of kidney macrophages in CKD can serve as a therapeutic opportunity to mitigate disease progression.